PENGGUNAAN TEKNIK PCR DAN RFLP UNTUK DETEKSI DAN ANALISIS KERAGAMAN VIRUS GEMINI PADA TANAMAN TOMAT YANG BERASAL DARI BERBAGAI DAERAH DI JAWA BARAT DAN LAMPUNG - Sudiono , Sri Hendrastuti Hidayat, , Rusmilah Suseno2, dan Soemartono Sosromarsono (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2004)
The Technique of PCR and RFLP to detection and analysis geminivirus diversity on tomato from growing areas in West Java and Lampung. Geminivirus infection has been reported on various important crops, among others on tomato. Infected plant were collected from six tomato growing areas in West Java (Bandung, Segunung, Darmaga, Ciloto, Cibeuying, and Cisaat) and Lampung (Bandar Lampung). Polymerase chain reaction method using universal primers for geminiviruses were successfully amplified a 1.5 kb DNA fragment from diseased plants from Bandung, Cisaat, Ciloto and Cibeunying. Comparative model enzyme restriction showed that sample from Bandung, Cisaat, Ciloto are probably strains of the same virus.